The Plan as Eidos: Bramante’s Half-Drawing and Durand’s Marche - Celedón, Alejandra (Revistarquis, 2014)
ABSTRACT By confronting Bramante’s plan for St Peter Basilica (1503) with Durand’s “Method of Composition” - summarized in his Marche plate (1802) - a modern conceptualisation of the plan unfolds which can be explained through the philosophical notion of eidos: the Greek term for “idea”, “form” and “type”. Beyond its role as representation, and as system of projection, these drawings set forth a function as communication, and furthermore, as organisation of a larger entity than the drawings themselves. Between these two moments, developments in the natural sciences and the project of the encyclopaedia are crucial to the formation of the idea of the plan. A descriptive (and ekphrastic) nature is behind Bramante’s half-plan drawing, what Durand systematized under his method of composition (marche) locating the plan as the site for abstraction where the essential and typical form of an idea ought to emerge. The drawing of a plan becomes a metonymic process that makes visible the essential and fundamental organizing principles of its form and which arise from the operations undertaken within the plan itself, as opposed to external or metaphorical references. From Bramante to Durand the plan reveals its diagrammatic and typological nature, which allowed escalating from the scale of architecture to that of the city. These ways of discussing the plan enable to frame its potential in mediating the world of architectural objects and the larger scale of the city and the territory, a narrative that not only constructs certain archaeology of the plan, but also questions the relationship between drawing and particular modes of thinking and production of the discipline. RESUMEN Al confrontar el plan de Bramante para la Basílica de San Pedro (1503) con el “Método de Composición” de Durand - resumido en su dibujo Marche (1802) - emerge una conceptualización moderna de la Planta, la cual se explica a través de la noción filosófica de eidos: el término griego para referir a “idea”, “forma” y “tipo”. Más allá de su función como representación, y como sistema de proyección, estos dibujos exponen una comunicativa, y más aún, organizativa de una entidad mayor que los dibujos mismos. Entre estos dos momentos; los desarrollos en las ciencias naturales y el proyecto de la enciclopedia son cruciales para la formación de la idea de la planta. Un carácter descriptivo (y ecfrástico) está detrás de la media-planta de Bramante, lo que Durand sistematizó bajo su método de composición (marche) ubicando la planta como el sitio para la abstracción, donde la forma esencial y típica de una idea debe emerger. El dibujo de la planta se convierte en un proceso metonímico que hace visibles los principios esenciales y fundamentales de organización de su forma y que surgen de las operaciones realizadas en la planta misma, en oposición a referencias externas o metafóricas. De Bramante a Durand, la planta revela su naturaleza esquemática y tipológica que le permite escalar desde la arquitectura a la escala de la ciudad. Estas maneras de discutir la planta permiten encuadrar su potencial en la mediación del mundo de los objetos arquitectónicos y la escala más grande de la ciudad y el territorio; una narrativa que no sólo construye cierta arqueología de la planta, sino que también cuestiona la relación entre el dibujo y los particulares modos de pensar y producir de la disciplina.